2014
DOI: 10.1097/01.asw.0000453728.12032.6f
|View full text |Cite
|
Sign up to set email alerts
|

Leg Ulcer Treatment Outcomes with New Ovine Collagen Extracellular Matrix Dressing

Abstract: The purpose of this study was to describe the rate of closure observed in venous leg ulcers during treatment with ovine collagen extracellular matrix dressings and compression. Fourteen patients with 23 wounds were retrospectively evaluated with respect to healing rates, time to closure, and weekly facility charge fees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Data from preliminary case series suggest that clinicians may achieve better outcomes in chronic wound healing in a shorter timeframe using a broad-spectrum ovine-based CECM dressing compared to previous available treatments. 17,34 Controlled clinical trials are needed to further analyze the comparative and cost-effectiveness of ovine-based CECM dressings in various wound types.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Data from preliminary case series suggest that clinicians may achieve better outcomes in chronic wound healing in a shorter timeframe using a broad-spectrum ovine-based CECM dressing compared to previous available treatments. 17,34 Controlled clinical trials are needed to further analyze the comparative and cost-effectiveness of ovine-based CECM dressings in various wound types.…”
Section: Discussionmentioning
confidence: 99%
“…3,34 In a study, including venous ulcers, diabetic foot wounds, and incisional wounds, Liden and May 35 reported 50% closure at 12 weeks with ovine-based CECM dressings with an average surface area reduction of 73.4%. Bohn and Gass 17 reported a healing rate of 97% of VLUs at 12 weeks with weekly application of CECM dressing and compression; 50% of wounds were closed by 7-8 weeks using CECM dressings. Authors suggested that compared with other collagen dressings requiring at least twice weekly application, the once weekly application of CECM dressings saved healthcare system dollars in terms of reduced facility fees, material costs, and home nursing visits.…”
Section: Effectiveness Of Collagen Dressings In Treating Vlusmentioning
confidence: 99%
See 3 more Smart Citations